2016
DOI: 10.1103/physrevb.94.144501
|View full text |Cite
|
Sign up to set email alerts
|

Spin susceptibility of Andreev bound states

Abstract: We calcuate electronic spin susceptibility and spin-lattice relaxation rate in singlet superconductor near a pairbreaking surface, or in a domain wall of the order parameter. We directly link presence of high-density Andreev bound states in the inhomogeneous region, combined with coherence factors, to enhancement of the susceptibility above the normal state's value for certain q vectors. Beside the dominant peak at ferromagnetic vector q = 0, we find significant enhancement of antiferromagnetic correlations at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…Mayaffre et al recently performed high-field nuclear magnetic resonance (NMR) measurements for a magnetic field parallel to the conducting plane, in κ-(BEDT-TTF) 2 Cu(NCS) 2 , which is one of the candidates for realizing the FFLO state, and they found a clear enhancement of the nuclear spin-lattice relaxation rate 1/T 1 in the field range between the Pauli-limiting field H P and H c2 (T ) [9], indicated by the appearance of the sharp bound states located away from E F . The enhancement of 1/T 1 suggested the formation of FFLO state, and it is in good agreement with the 1/T 1 calculation [10]. Therefore, taking 1/T 1 measurements around H c2 is recognized as a valuable method for searching the FFLO state.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…Mayaffre et al recently performed high-field nuclear magnetic resonance (NMR) measurements for a magnetic field parallel to the conducting plane, in κ-(BEDT-TTF) 2 Cu(NCS) 2 , which is one of the candidates for realizing the FFLO state, and they found a clear enhancement of the nuclear spin-lattice relaxation rate 1/T 1 in the field range between the Pauli-limiting field H P and H c2 (T ) [9], indicated by the appearance of the sharp bound states located away from E F . The enhancement of 1/T 1 suggested the formation of FFLO state, and it is in good agreement with the 1/T 1 calculation [10]. Therefore, taking 1/T 1 measurements around H c2 is recognized as a valuable method for searching the FFLO state.…”
supporting
confidence: 80%
“…First, the normalized increase of 1/T 1 T , (1/T 1 T ) peak /(1/T 1 T ) normal , differs. Although 1/T 1 T increased almost twofold in the case of κ-(BEDT-TTF) 2 Cu(NCS) 2 , in the present case (1/T 1 T ) peak /(1/T 1 T ) normal estimated from the magnetic field dependence of 1/T 1 T is ∼ 1.2 for H c and ∼ 1.3 for H ⊥ c. The increase in ratio of 1/T 1 T depends on the SC gap symmetry and the details of the Fermi surfaces of the systems [10]. Second, the enhancement of 1/T 1 T was observed for H c and H ⊥ c in CeCu 2 Si 2 while this enhancement was only observed for H conducting plane in the case of κ-(BEDT-TTF) 2 Cu(NCS) 2 .…”
Section: Pacs Numbersmentioning
confidence: 44%
“…Recently, a high-field NMR experiment [30] has shown that these spin-polarized ABS produce a huge enhancement of the NMR relaxation rate 1/T 1 (Fig 6a), providing the first microscopic characterisation of an FFLO phase. It turns out that this effect only occurs in a limited range of relatively high temperature, which has been consistently explained by theory [181], showing that this enhancement comes from the scattering of electronic spins between the bound and continuum states. A new compound with much smaller H c2 values, β"-(BEDT-TTF) 2 SF 5 CH 2 CF 2 SO 3 , has been recently investigated [182] by NMR, confirming the nuclear spin-lattice relaxation results obtained in [30] are ubiquitous of the FFLO phase, and observing a lineshape compatible with a single-q modulated superconducting phase.…”
Section: Exotic Superconductivity a Fflo State In κ-(Bedt-ttf)2cu(scn)2supporting
confidence: 57%
“…At 27 T, the system remains normal down to the lowest temperature investigated (1.4 K), while at 22 T, the system enters from the normal state into the FFLO phase. The huge peak in (T1T ) −1 is due to the Andreev bound states present in the FFLO phase [30,180,181]. Inset: Simulation of the (T1T ) −1 peak due to the Andreev bound states.…”
Section: Exotic Superconductivity a Fflo State In κ-(Bedt-ttf)2cu(scn)2mentioning
confidence: 99%
“…However, it is noted that a strong enhancement in 1/T 1 T just below H c2 (T ), which is regarded as a hallmark of the FFLO state in κ−(BEDT-TTF) 2 Cu(NCS) 2 , 17) was not observed for UPd 2 Al 3 . It was shown from a theoretical study 18) that the enhancement in 1/T 1 T originates from the presence of the Andreev bound state inside the SC gap, and that the magnitude of the enhancement depends on the SC gap structure. Therefore, we consider that the different behavior of 1/T 1 T could be interpreted with the difference in SC gap structures of κ−(BEDT-TTF) 2 Cu(NCS) 2 and UPd 2 Al 3 .…”
mentioning
confidence: 99%